2012
DOI: 10.1136/heartjnl-2012-303022
|View full text |Cite
|
Sign up to set email alerts
|

Attendance at cardiac rehabilitation is associated with lower all-cause mortality after 14 years of follow-up

Abstract: Objective To investigate whether attendance at cardiac rehabilitation (CR) independently predicts all-cause mortality over 14 years and whether there is a doseresponse relationship between the proportion of CR sessions attended and long-term mortality. Design Retrospective cohort study. Setting CR programmes in Victoria, Australia Patients The sample comprised 544 men and women eligible for CR following myocardial infarction, coronary artery bypass surgery or percutaneous interventions. Participants were track… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
111
0
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(120 citation statements)
references
References 27 publications
3
111
0
6
Order By: Relevance
“…3). In cardiovascular patients, it is clear that attending a higher proportion of cardiovascular rehabilitation sessions confers greater longterm benefit than attending fewer sessions [43][44][45]. Our findings were consistent with those of previous studies in cardiovascular patients.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…3). In cardiovascular patients, it is clear that attending a higher proportion of cardiovascular rehabilitation sessions confers greater longterm benefit than attending fewer sessions [43][44][45]. Our findings were consistent with those of previous studies in cardiovascular patients.…”
Section: Discussionsupporting
confidence: 83%
“…On the other hand, some other studies regarding prevention, e.g., in the general sedentary population, [40] patients with cancer, [41,42] and cardiovascular disease patients, [43][44][45] used the proportion of exerciserelated program attendance as a predictor of outcome. In the present study, the median proportion of attendance at the management program was 75%, which was within the range reported in other studies [41,42,45] (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, cardiac rehabilitation programs with an exercise training component such as continuous aerobic exercise training (CAET) were found to be safe and to improve prognosis in CHD patients [7][8][9][10][11]. The additional clinical benefits of exercise training in CHD patients are well documented and include improvements in cardiovascular, lung and skeletal muscle functions, endurance, quality of life, inflammation, depressive symptoms, stress and cognitive functions [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…These studies have shown that only 20-40% of candidates actually attend cardiac rehabilitation programmes. The non-attenders have about a 30% worse survival than do attenders, a much worse survival than seen in the control groups of randomised controlled studies [69][70][71][72][73][74][75][76][77]. Furthermore, the reduction in mortality was more marked than any reduction in cardiac deaths, cardiac morbidity or cardiac interventions.…”
Section: Uptake and Utilisation: Cohort Studiesmentioning
confidence: 87%